THE EFFECT OF LEARNING MODELS MISSOURI MATHEMATICS PROJECT WITH TWO STAY TWO STRAY METHODS FOR MATHEMATICAL PROBLEM SOLVING ABILITY OF STUDENT IN 7 th GRADE SMP N 1 TAWANGMANGU - Rachma Hanan Tiasto; Elly Arliani (Jurnal Pedagogi Matematika, 2016)
AbstractThis study aims to determine the effect of learning models of Missouri Mathematics  Project with Two Stay Two Stray methods for mathematical problem solving ability of grade VII students of SMP N 1 Tawangmangu. The method in this study is a quasi experimental research design with pre-test post-test design group. The population in this study were all students  of  grade  VII  of  State  Junior  high  School  1  Tawangmangu.  The  sample  in  this  research  is  grade  VII  F  had treatment with Missouri Mathematics Project learning models of Two Stay Two Stray method as the experimental class and  grade  VII  G  as  the  control  class  who  receive  conventional  learning  treatment.  This  instrument  were  tests  and observation sheets. The hypothesis test method used was one sample test and t-test independent sample. Based on the results of data analysis, the value of tcount= 7,171 t(0.05:31)=2,0395 with a significance level of 5% thus Ho rejected which means that the learning model of Missouri Mathematics Project with Two Stay Two Stray method was effective in terms of students’ mathematical problem solving ability. The  results of data analysis obtained the value of tcount= 6,476 t(0.05:62)=1,998971 thus Ho was rejected. This means that the learning model of Missouri Mathematics Project with Two Stay  Two  Stray  method  affected  the  ability  of  students'  mathematical  problem  solving.Keywords: Missouri Mathematics Project, Two Stay Two Stray, problem solving ability